A implantação do reuni e o seu impacto na evasão discente - Moura, Ludmila Guerra de (2018)
The demand for higher education increases proportionately to the nation development. One of ways for governments supply this demand is to establish public policies focused on this type of education, and the Federal University Restructuring and Expansion Support Program (REUNI) is an example of such policies. The main purpose of REUNI was to create conditions for the expansion and permanence in public higher education. However, the way taken by an university student, from his admission to receiving the University Degree, can present several mishaps, among them, the abandonment of studies. The fight against dropout in higher education is one of points worked by the REUNI program. As a way to contribute to the evaluation of this public educational policy and to provide subsidies for better university management, this research aims to analyze the impact of REUNI on student dropout at the Federal University of Uberlândia in the year 2000 to 2017. In the present work, themes such as Public Policies, Public Policy Cycle, Expansion of Higher Education, REUNI and Student Evasion were discussed. The research is of the descriptive type and qualitative and quantitative methods were used. The secondary data used in this research come from the database made available by the Board of Administration and Academic Control. These data were processed and adjusted for the statistical analysis, using the descriptive statistics to interpret them. The results showed that the average rates of avoidance in the courses created or that had an increase in the number of vacancies with the implementation of the REUNI are higher than the indexes of the courses that already existed in the institution. However, in relation to those that had an increase in the offer by REUNI, which were courses that, historically, had already averted higher average non-REUNI courses. As for the student's admission to the institution, it was detected that there is greater evasion among the candidates who chose the Unified Selection System (SISU) as a form of selection, and the dropout rates of the students per vestibular were lower. The average drop in the period from 2001 to 2012 was around 29.11%. Data analyzes also showed that, in the period of implementation of the REUNI, from 2008 to 2012, the courses in Mathematics and Natural Sciences are the ones with the highest average percentage of dropout in the study period, 75.70%, and the area Medical and Health, which have a lower percentage, 16.31%. The courses that stood out with the highest average drop in the REUNI implementation period were: Physics (99.21%); Materials Physics (88.26%) and Mathematics (83.91%). From this work, two technological products originated, which are: the Executive Summary and the planning of a workshop, both destined to the Graduate Rectorate.